Seleção de famílias e progênies de irmãos completos de cana-de-açúcar para atributos tecnológicos e de produção pelo método de REML/BLUP - Xavier, Mauro Alexandre; Perecin, Dilermando [UNESP]; Alvim, Karen Rodrigues de Toledo [UNESP]; Landell, Marcos Guimarães de Andrade; Arantes, Flávio Cese [UNESP] (Inst Agronomico, 2014)
The objective of this study was to assess families and highlight the superior progenies of sugarcane originating from 38 biparental crosses for the following attributes: tons of cane per hectare (TCH), tons of biomass per hectare (TBIOH), brix (% cane juice), fiber content, purity, pol and total recoverable sugar (TRS). The data were analyzed by mixed model REML / BLUP in the REML (Restricted Maximum Likelihood) allowed us to estimate genetic parameters and BLUP (best linear unbiased prediction) to predict the additive and genotypic values. The best family for the attributes TCH and TBIOH was 41, whose parents are cultivars IACSP022019 x CTC9. In individual selection for TCH, the plant number 3 of Block 2, the crossing 78, showed the best results. To TBIOH the plant number 33, Block 1, family 41, showed the best results. Families 40, 41, 43, 68, 69, 79, 91, 92 and 147, were higher for the variables brix, pol, purity, and ATR, where as 85 families, 147, 148, 149, 161, 163, 177, 178, 179, and 183 were higher for fiber. The family 147 whose parents are IACSP042286 x IACSP963055, showed three progenies ranked among the top ten for both brix, and for fiber, which identifies the combination as a potential source of progenies for bioenergy production.

O objetivo deste trabalho foi avaliar as famílias e destacar as progênies superiores de cana-de-açúcar oriundas de 38 cruzamentos biparentais para os seguintes atributos: tonelada de colmos por hectare (TCH), toneladas de biomassa por hectare (TBIOH), brix (% caldo da cana), teor de fibra, pureza, pol e açúcar total recuperável (ATR). Os dados foram analisados via modelos mistos REML/BLUP, em que o REML (Máxima Verossimilhança Restrita) permitiu estimar parâmetros genéticos e BLUP (Melhor Predição Linear Não Viciada) permitiu predizer os valores aditivos e genotípicos. A melhor família para os atributos TCH e TBIOH foi a 41, cujos parentais são as cultivares IACSP022019 x CTC9. Na seleção individual para TCH, a planta de n. 3 do bloco 2, do cruzamento 78 foi a que apresentou o melhor resultado. Para TBIOH, a planta n. 33, do bloco 1, da família 41 foi superior. As famílias 40, 41, 43, 68, 69, 79, 91, 92 e 147 foram superiores para as variáveis brix, pol, pureza e ATR, enquanto que as famílias 85, 147, 148, 149, 161, 163, 177, 178, 179 e 183 foram superiores para fibra. A família 147, cujos parentais são IACSP042286 x IACSP963055, mostrou três progênies entre as dez melhores tanto para brix quanto para fibra, o que identifica essa combinação como potencial fonte de progênies para produção de bioenergia.
Selecting families and full-sib progenies of sugarcane for technological attributes and production by the method of REML/BLUP
Keywords: Saccharum spp.; Mixed models; Crop breeding; Saccharum spp.; Modelos mistos; Melhoramento genético